The evaluation of effectiveness on education and training program - Rangga Ramdhoany Alsyaibany (Journal of Educational and Learning Studies, 2019)
This research aims to evaluate an education and training program in a government institution, specifically in PNT Education and Training Program of Bauxite Ore in West Borneo which is conducted every year by Pusdiklat MINERBA Bandung, Indonesia. The research purpose is to describe the effectiveness of the existing education and training program (Diklat) so that it could be improved to complete the implementation of similar programs in the future. Specifically, this research focused on measuring level of effectiveness from three aspects, which includes the reaction, learning, and potential behavioural changes aspect. The data was collected by using quantitative approach with descriptive evaluative method. There were 15 participants involved in this research. The result showed that the reaction level of participant toward the Diklat program was quite effective (63.39%).  This aspect has a quite significant achievement in that there was a positive attitude of most of the participants in implementing the result of the program in workplace. Learning level of the participant increased with x ̅= 0.42 based on the pre-test and post-test result, while the measurement of potential behaviour changes level showed that the average score of participants' belief could be classified into high level (74%). In conclusion, the program had been conducted well and could be classified into effective level category.